Knowledge Regarding Various Government Child Health Schemes Among Mothers in Kerala: A Descriptive Study - Vidya E.; Leji K. Jose; Sajina T.P.; Ponnamma K.M. (International Journal of Evidence Based Nursing And Practices, 2024)
The study was conducted to check the knowledge regarding child health schemes among mothers of children who were attending pediatric outpatient department of Institute of Maternal and Child Health. The primary aim of the research was to evaluate mothers' understanding of child health programs, explore the relationship between their knowledge and various sociodemographic factors, and develop an informational booklet on child health schemes. The study involved 250 mothers, who were chosen through consecutive sampling. A questionnaire measured their knowledge of child health schemes. Data were gathered from January 10, 2019, to February 2, 2019. Both descriptive and inferential statistics methods were employed to process the data. The study's results showed that 56.6% of the mothers possessed moderate knowledge of child health schemes. Out of 250 mothers, 47% knew about the Rashtriya Swasthya Bima Yojana (RSBY) scheme, while 23.6% had awareness of the Hridhyam scheme. Additionally, 32.7% of the mothers had average understanding of the Thalolam scheme, and 17.1% demonstrated good knowledge of the RSBY scheme. The association between knowledge of mothers regarding child health schemes and number of children, age of mother, income, occupation, and primary source of source of health information are found significant at the 0.001 level.
Keywords: Arogyairanam; Hridhyam; Janani Shishu Suraksha Karyakram (JSSK); Knowledge; Rashtriya Bal Swasthya Karyakram (RBSK); Rashtriya Swasthya Bima Yojana (RSBY); Thalolam; child health schemes